2018
DOI: 10.17265/2328-7136/2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evaluation of Retinal Artery Occlusion Patients Who Applied Hyperbaric Oxygen Treatment

Abstract: Introduction: Hyperbaric oxygen treatment (HBOT) is one of the treatment modalities for retinal artery occlusion (RAO). HBOT may be beneficial if initiated within 2-12 hours of onset of symptoms. The objective of this study was to evaluate the usefulness of HBOT on the patients who had applied to our center for HBOT with an RAO diagnose. Methods: Sixteen patients were included in this study for a three-year period those were applied HBOT with RAO diagnosis. HBOT sessions of these patients had been started as q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
1
1
Order By: Relevance
“…Additionally, other OCT parameters we measured were not associated with visual prognosis either. While several previous studies have indicated that the duration between the onset of initial symptoms and the commencement of HBOT correlates with an improvement in BCVA, (17,32) our study did not observe this association. The visual prognosis of our patients was solely associated with baseline BCVA.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, other OCT parameters we measured were not associated with visual prognosis either. While several previous studies have indicated that the duration between the onset of initial symptoms and the commencement of HBOT correlates with an improvement in BCVA, (17,32) our study did not observe this association. The visual prognosis of our patients was solely associated with baseline BCVA.…”
Section: Discussioncontrasting
confidence: 99%
“…To date, no standard treatment has been established for CRAO. Several treatments, such as pentoxifylline, carbogen inhalation, sublingual isosorbide dinitrate, ocular massage with a three-mirror contact lens, acetazolamide, mannitol, methylprednisolone, tissue plasminogen activator, and neodymium: yttrium-aluminum-garnet laser, as well as surgical modalities, such as anterior chamber decompression and pars plana vitrectomy with removal of the embolus, have been suggested [ 2 , 37 , 38 , 39 , 40 ].…”
Section: Hbot In Retinal Diseasesmentioning
confidence: 99%